Same old story: Hungary’s development over the 2000–2020 period - Zoltán Bartha (Theory, Methodology, Practice, 2022)
Hungary’s convergence to the developed western economies has been much slower than initially expected. Applying the FOI model, this study investigates whether there were any changes in the convergence process during the first two decades of the 21st century. It is found that the future potential (influencing the long-term competitiveness of the economy) and inside potential (determining the current well-being of the country) of the Hungarian economy did not improve at all compared to the 34 countries that were OECD members in 2010. Hungary’s position is in fact very poor; it is ranked 33rd in both areas. The country does somewhat better in the outside potential (characterising its world market position), prompting the conclusion that Hungary follows a growth model that is focused on external resources. This feature is not new, however: the same development model patterns were detected in 2010, too.